Genotoxicity and antigenotoxicity of the methanol extract of Cleistocalyx nervosum var. paniala seed using a Salmonella mutation assay and rat liver micronucleus tests - Wanida Inboot (2018)
Clesitocalyx nervosum var. paniala, an edible fruit found in some parts of Southeast Asia including Thailand, contains high amounts of polyphenols and has multiple biological activities. The purposes of this study were to evaluate the genotoxic and antigenotoxic effects of methanol extracts of C. nervosum seeds via a Salmonella mutation assay and a rat liver micronucleus test. C. nervosum extract was not mutagenic to Salmonella typhimurium strains TA98 and TA100 in both the presence and absence of metabolic activation. Furthermore, C. nervosum seed extract presented antigenotoxicity against aflatoxin B1, MeIQ and AF-2 induced mutagenesis. Clastogenicity and anticlastogenicity of C. nervosum seed extracts were determined in rat livers. Male wistar rats were divided into 6 groups. Groups 1 and 3 were treated with 5% tween-80 as a vehicle control. Group 2 received 1,000 mg/kg bw of methanol seed extract and groups 4-6 were fed with 20, 100 and 1,000 mg/kg bw of seed extracts, respectively for 21 days. At day 15 and 18 of the experiment, treated rats in groups 3-6 were intraperitoneally injected with 30 mg/kg bw of diethylnitrosamine to initiate hepatocarcinogenesis. At day 22, all rats were partially hepatectomized to amplify mutated hepatocytes. C. nervosum seed extract did not affect micronucleus formation in rat livers, but did slightly decrease the frequencies of micronucleated hepatocytes of diethylnitrosamine treated rats. In conclusion, the methanol extract of C. nervosum seed may contain chemopreventive compounds against carcinogenesis. © 2012 The Korean Society of Toxicogenomics and Toxicoproteomics and Springer Netherlands.